Over-expression of Slc30a8/ZnT8 selectively in the mouse α cell impairs glucagon release and responses to hypoglycemia. Issue 1 (December 2016) - Solomou, Antonia; Philippe, Erwann; Chabosseau, Pauline; Migrenne-Li, Stephanie; Gaitan, Julien; Lang, Jochen; Magnan, Christophe; Rutter, Guy
Abstract Background The humanSLC30A8 gene encodes the secretory granule-localised zinc transporter ZnT8 whose expression is chiefly restricted to the endocrine pancreas. Single nucleotide polymorphisms (SNPs) in the humanSLC30A8 gene have been associated, through genome-wide studies, with altered type 2 diabetes risk. In addition to a role in the control of insulin release, recent studies involving targeted gene ablation from the pancreatic α cell (Solomou et al., J Biol Chem 290(35):21432-42) have also implicated ZnT8 in the control of glucagon release. Up to now, however, the possibility that increased levels of the transporter in these cells may impact glucagon secretion has not been explored. Methods Here, we use a recently-developed reverse tetracyline transactivator promoter-regulated ZnT8 transgene to drive the over-expression of human ZnT8 selectively in the α cell in adult mice. Glucose homeostasis and glucagon secretion were subsequently assessed both in vivo during hypoglycemic clamps and from isolated islets in vitro. Results Doxyclin-dependent human ZnT8 mRNA expression was apparent in both isolated islets and in fluorescence-activated cell sorting- (FACS) purified α cells. Examined at 12 weeks of age, intraperitoneal glucose (1 g/kg) tolerance was unchanged in transgenic mice versus wild-type littermates (n = 8-10 mice/genotype, p > 0.05) and sensitivity to intraperitoneal insulin (0.75U/kg) was similarly unaltered in transgenic animals. In contrast, under hyperinsulinemic-hypoglycemic clamp, a 45 % (p < 0.001) reduction in glucose infusion rate was apparent, and glucagon release was significantly ( 40 %, p < 0.01) impaired, in transgenic mice. Correspondingly, examined in vitro, glucagon secretion was significantly reduced ( 30 %, p < 0.05) from transgenicversus control islets at low, stimulatory glucose concentrations (1 mM, p < 0.05) but not at high glucose (17 mM) glucose (p > 0.05). Over-expression of ZnT8 in glucagonoma-derived αTC1-9 cells increased granule free Zn2+ concentrations consistent with a role for Zn2+ in this compartment in the action of ZnT8 on glucagon secretion. Conclusions Increased ZnT8 expression, and a likely increase in intragranular free Zn2+ concentration, is deleterious in pancreatic α cells for stimulated glucagon release. These data provide further evidence that type 2 diabetes-associated polymorphisms in theSLC30A8 /ZnT8 gene may act in part via alterations in glucagon release and suggest that ZnT8 activation may restrict glucagon release in some settings.